Computer Vision Syndrome among Children Using Online E-Learning during the COVID-19 Pandemic - Mallik, Chinmoy (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Since the declaration of the lockdown due to COVID-19, the usage of digital devices has gone up across the globe, resulting in a challenge for the visual systems of all ages. The aim of this study was to determine frequency, symptoms frequency and associated risk factors of Computer Vision Syndrome (CVS) among children attending online classes during COVID-19 pandemic. Materials and methods: The online electronic survey form was prepared on the Google app. Children/parents were asked to indicate the total duration of digital device use before and during COVID era. The symptoms of CVS, its severity and frequency were recorded and measured with the Computer Vision Syndrome Questionnaire. Results: One hundred and sixty four parents responded to the questionnaire, of these 124 were complete. Mean age of children was 14±3.01 years. Mean duration of digital device used during COVID era was 34.11±2.08 hours which was more than pre COVID era (0.98±0.24 hours). 36.29% used digital devices >5 hours in COVID era as compared to 0% before COVID era. The most common digital device used was smartphones (62.1%). Sixty seven children (54.03%) were attending online classes for >2 hours per day. 50% of the children had CVS. Of these 25% were mild, 12.9% moderate and 12.1% of severe grade. Most common symptoms were itching and headache. Multivariate analysis revealed age >14 years, male gender, smartphone use, use of device >5 hours and mobile games >1 h/day as independent risk factors for CVS in children. Conclusion: There is an increased prevalence of CVS among children in COVID era. Awareness about prevention of CVS should be stressed and going forward, measures to bring these adverse effects to a minimum should be explored. JCMCTA 2021 ; 32 (1) : 48-52